Efficacy of a theory-based and tailored mHealth intervention promoting walking behavior: a preliminary randomized controlled trial - Roberta Adorni; Francesco Zanatta; Silvia Serino; Maria Elide Vanutelli; Daniela Caso; Marco D’Addario; Patrizia Steca (Scientific Reports)
Abstract Physical inactivity is one of the core risk factors for non-communicable diseases. Scaling up health interventions using theoretically-driven and smart-enabled approaches is critical to strengthening prevention strategies. This study evaluated the efficacy of an ad-hoc developed mobile health (mHealth) intervention, which adopts a theory-based and tailored communication approach and targets walking behavior change. A convenience sample of physically inactive adults (n = 193) participated in a 30-day randomized trial. Before the intervention, psychological variables selected from the Health Action Process Approach (HAPA) were evaluated to profile participants and develop tailored materials. Allocation (1:1:1) was performed to one of three conditions: (i) tailored communication based on the HAPA model (HAPA-T group); (ii) non-tailored communication focused on wellbeing (Wellbeing-NT group); (iii) no-communication group. All participants were also exposed to goal-setting (i.e., reaching 7,000 steps daily) and self-monitoring. A repeated measures ANOVA was performed to monitor the mean weekly steps over the 30-days trial period within and among the three conditions. Overall, participants reported significant improvements in walking behavior over the trial period. Although no significant outcome differences were observed among the three experimental conditions, differential patterns of walking emerged from the study groups, with the HAPA-T group showing a wider increase at the final time-point. The intervention showed a significant overall impact, unveiling crucial procedural strengths and limitations. These were discussed to orient optimized implementation for future digital full-scale trials. Trial Protocol Registration ClinicalTrials.gov registration ID NCT05620888 (17th November 2022; https://clinicaltrials.gov/study/NCT05620888 ).